1978
DOI: 10.18174/njas.v26i2.17100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen on crop development and grain growth of winter wheat in relation to assimilation and utilization of assimilates and nutrients.

Abstract: Grain growth and yield components of winter wheat cv. Lely were studied in a field experiment in 1976 with 4 rates of N (50, 100, 100 + 50 or 100 + 100 kg N/ha). Growing conditions were characterized by a high level of solar radiation, warmth, ample nutrient supply and no damage by diseases. N raised grain number/m2 from 16 700 to 20 600 and grain yield from 640 to 821 g dry wt./m2. Grain growth duration was short, due to warmth, but the rate of the grain filling was very high (from 24.0 to 29.2 g/m2 day durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
41
1
4

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 18 publications
9
41
1
4
Order By: Relevance
“…Bodson et al [33] studied the split of N fertilizer on wheat and found that applying N fertilizer twice at stem elongation and at flag leaf stages gave similar yields with higher grain quality compared to traditional practice with 3 applications at tillering, stem elongation and leaf flag stages. Furthermore, a number of studies showed the potential of increasing grain yield and grain protein through late-season N application under rainfed conditions [34,35] and in irrigated conditions [36,37]. These authors found that the yield increase with N late-application depended on the native soil N supply, previous soil N uptake, plant developmental stage, and yield potential.…”
Section: Introductionmentioning
confidence: 99%
“…Bodson et al [33] studied the split of N fertilizer on wheat and found that applying N fertilizer twice at stem elongation and at flag leaf stages gave similar yields with higher grain quality compared to traditional practice with 3 applications at tillering, stem elongation and leaf flag stages. Furthermore, a number of studies showed the potential of increasing grain yield and grain protein through late-season N application under rainfed conditions [34,35] and in irrigated conditions [36,37]. These authors found that the yield increase with N late-application depended on the native soil N supply, previous soil N uptake, plant developmental stage, and yield potential.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen fertilizer is a key input to North European wheat production, with an average 197 kg N/ha applied to wheat crops in the UK in 2002 (Goodlass et al 2003). Nitrogen in the crop is strongly correlated with canopy size and duration, light interception, grain numbers per unit area and thus grain yield (Spiertz & Ellen 1978;Evans 1993;Peltonen 1993;Sylvester-Bradley et al 1997). Additionally, N applications can increase grain protein concentration, increasing end use value, especially for milling markets (Gooding & Davies 1997).…”
Section: Introductionmentioning
confidence: 99%
“…High yielding wheat cultivars grown under temperate climatic conditions in the Flevopolder, The Netherlands (photo taken by the author). For details: see Spiertz and Ellen (1978).…”
Section: Food Security and Land And Nitrogen Usementioning
confidence: 99%
“…This value is usually high in cereals and tuber crops, e.g. : 0.60-0.80 for wheat (López-Bellido et al, 2008;Spiertz and Ellen, 1978) and 0.70-0.80 for potato (Biemond and Vos, 1992)), but somewhat lower in legumes (Chapman et al, 1985). Cereals do reallocate N from the leaves to the grains, while in root crops most N is retained in crop residues.…”
Section: Nitrogen Photosynthesis and Plant Growthmentioning
confidence: 99%